(untitled) (Revista Electrónica REDINE, 2018)
This research project with positivist approach whose nature was a field study of a descriptive type, with transversal design and located in the line of management in teaching, education and research. It was proposed as a General Objective: Determine the academic productivity of the professors assigned to the nursing department in terms of: Scientific Activity and Scientific Production. Deanship Health Sciences. Centroccidental University Lisandro Alvarado. The population under study was composed of 44 professors assigned to the nursing department. The survey was used as a research method and the questionnaire technique was applied to socialize with those investigated through an instrument with questions of different response options. Which was applied once obtained the informed consent on the part of the investigated ones. The data collected were tabulated, analyzed and presented following the descriptive statistical process and the analysis related to the theoretical focus of the study, among the most outstanding conclusions is that the scientific productivity among the professors assigned to the Department of Nursing is deficient 33% of academic productivity in the area of ​​Scientific Activity and Production which is located on the scale of measurement presented in the deficient line (21 to 40) , so it is necessary to reorient the policies, plans and objectives in terms of research.